Performance analysis of electronic national agricultural markets: some evidence from Odisha - Chandan Khandagiri; Elumalai Kannan (Agricultural Economics Research Review, 2023)
This paper analyses the effect of electronic agricultural markets on commodity arrivals and price volatility. Compared to that in the period before the National Agricultural Market (eNAM), market arrivals of commodities declined later, average monthly prices increased, and farmers received lower prices on average. The paper also analyses the influences on farmers’ decision to participate in electronic trading, and it finds that farmers’ education, small landholding size, and age had a positive and significant effect on participation. The eNAM needs to include more markets, raise awareness about its features, and train farmers and traders to make their participation effective.